Expression of semaphorin 6D in gastric carcinoma and its significance - Zhao, Xiang-Yang (Baishideng Publishing Group Co., Limited, 2006)
AIM: To investigate the protein and mRNA expression of semaphorin 6D in gastric carcinoma and its significance. METHODS: The protein and mRNA expression of semaphorin 6D was detected by semi-quantitative rever-se transcription PCR and Western blotting respectively in 30 cases of gastric carcinoma and normal gastric mucosa. RESULTS: The protein and mRNA expression of semaphorin 6D in gastric carcinoma was significantly higher than that in normal gastric mucosa (0.24 ± 0.06 vs 0.19 ± 0.07, 0.26 ± 0.09 vs 0.20 ± 0.10, P < 0.05). CONCLUSION: Semaphorin 6D may play an important role in the occurrence and development of gastric carcinoma, and is related to tumor angiogenesis.